Fabrication of a cost-effective MEMS-based piezoresistive cantilever sensor for gait movement analysis - Ahmad Fitri Anuar, Mahayudin (Kementerian Pendidikan Tinggi (KPT), Malaysia, 2018)
Link to publisher's homepage at http://www.mohejournal.com/index.php/mohe